TECHNOLOGY TRANSFER IN INDONESIA : LEGAL PERSPECTIVE (UUM Journal of Legal Studies, 2014)
This study aimed to analyses technology transfer in Indonesia. As we have indicated, Indonesian Patents Law, No. 14 of 2001, have failed to create technology transfer for Indonesia. Even though the transfer of technology is strongly campaigned as a principal means of relieving world poverty, there is no reliable and credible evidence that shows a significant correlation between technology transfer under the patent regime and the collective mastery of a nation to access information, knowledge and technology (INT) effectively in order to improve the quality of people’s lives.Kajian ini bertujuan untuk membahas pemindahan teknologi di Indonesia. Seperti yang telah kita lihat, ketentuan Paten No. 14 Tahun 2001 ini, telah gagal melakukan pemindahan teknologi terhadap Indonesia. Sekalipun pemindahan teknologi adalah sangat kuat diserukan sebagai suatu prinsip, dengan tujuan utama mengurangi kemiskinan dunia, tidak dapat dipercayai dan tidak ada bukti yang menunjukkan satu kaitan yang kuat antara pemindahan teknologi di bawah aturan paten dan penguasaan bersama dari suatu bangsa untuk mendapatkan informasi, pengetahuan dan teknologi efektif guna meningkatkan kualitas dari kehidupan rakyat.Keywords: Sistem paten, pemindahan teknologi.